الإستراتيجية التنافسية والخصائص التنظيمية والسلوكية لدائرة التسويق وأثرها في الأداء التسويقي - محمد خير, سليم أبو زيد; زيادات, محمد عواد (Université de M'sila, 2010)
The major purposes of this research are: 1) studying the direct and indirect effect of organizational strategy on marketing performance, through marketing organization characteristics and marketing organization behavior, 2) studying the effect of marketing organization characteristics and marketing organization behavior on marketing performance. By conducted an empirical studied on Industrial companies located in Sahab city in Jordan. In order to collected the data, a questionnaire was designed and distributed among the study sample (150) organization. The data were analyzed by using descriptive statistics, path analysis and factor analysis. The most important findings of the study were: most of Jordanian companies follow differentiation strategy, there is indirect effect of differentiation strategy on marketing performance through marketing organization variables,. and there is indirect effect of cost focus strategy on marketing performance through organizational and behavioral characteristics of marketing department